2006
DOI: 10.1287/mnsc.1060.0547
|View full text |Cite
|
Sign up to set email alerts
|

Entry Strategies Under Competing Standards: Hybrid Business Models in the Open Source Software Industry

Abstract: The paper analyzes the strategies of software firms that have entered the open source (OS) field. The notion of the OS business model is discussed in the light of a substantial body of theoretical literature concerning strategic management and the economics of innovation, as well as specialized literature on OS. Empirical evidence based on a survey of 146 Italian software firms shows that firms have adapted to an environment dominated by incumbent standards by combining the offering of proprietary and OS softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
186
2
22

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(213 citation statements)
references
References 36 publications
3
186
2
22
Order By: Relevance
“…However, Lundell et al observed that companies with more than 250 employees seemed more conservative towards OSS adoption [12], Bonaccorsi et al found that size does not favor OSS adoption [1], and Ghosh et al found variations in the adoption of OSS over company size, countries, and sectors [6]. The relation between size and OSS adoption needs to be investigated in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Lundell et al observed that companies with more than 250 employees seemed more conservative towards OSS adoption [12], Bonaccorsi et al found that size does not favor OSS adoption [1], and Ghosh et al found variations in the adoption of OSS over company size, countries, and sectors [6]. The relation between size and OSS adoption needs to be investigated in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Without being able to provide any numbers representative for the whole population, an Italian study found that software companies using OSS commonly adapt or build on top of these OSS products [1].…”
Section: Related Workmentioning
confidence: 99%
“…Yet, an increasing number of managers and designers in firms see great promise in OS-related IT artifacts developed by global communities, and have started to adapt these to internal needs, contribute to their collective development, and build relationships with the communities (Bonaccorsi et al, 2006;Henkel, 2006;Dahlander and Wallin, 2006). Additionally, a design science approach to IS research needs to answer the question of how best to relate to the community to jointly build new and effective IT artifacts.…”
Section: Design and Relate: An Overview Of The Literaturementioning
confidence: 99%
“…A study of new entrants in the Italian software industry (Bonaccorsi et al, 2006) finds that entrepreneurship emerges on the fringes of OS software development, giving rise to new markets for products and services. Here, users design business models that involve community support, packaging, combining, selling artifacts, or providing services to other OS software users (see, for example, Fitzgerald 2006).…”
Section: Toward a New Research Framework For Design Sciencementioning
confidence: 99%
See 1 more Smart Citation